Vaccinal Prevention of Pneumococcal Infection in Children - A. A. Baranov; L. S. Namazova-Baranova; N. I. Briko; Y. V. Lobzin; V. K. Tatochenko; S. M. Kharit; M. V. Fedoseyenko; E. A. Vishnyova; L. R. Selimzyanova (Union of pediatricians of Russia, 2015)
It is known that before vaccination had been widely introduced pneumococcal infection was the cause of death of more than 1.5 mn people around the world annually, 40% of whom were infants. According to the World Health Organization (WHO), pneumococcal infection is the most dangerous of the vaccinally prevented diseases. Resistance of pneumococcus to antibacterial drugs is a global issue complicating control of pneumococcal infection around the world. Increasing resistance of the causative agent complicates treatment of patients with various forms of pneumococcal diseases, requires use of the second- and the third-line therapeutic antimicrobial drugs and increases duration of hospitalization and treatment costs. Vaccination is considered the main method of preventing antibiotic-resistant pneumococcus-induced infections. The authors present the newest opinions on vaccinal prevention of pneumococcus-induced diseases.